Public Debt and Economic Growth. Measuring the Long Run Impact in Latin America: 1970-2016 (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2020)
In this work, a measurement is made of the long-term impact of the total gross debt of the central government on the growth of the Real Gross Product for a group of Latin American countries, in the period 1970-2016. For this, cointegration contrasts are used and a dynamic panel data model (DOLS - Dynamic Old Last Squared) is estimated. The evidence indicates that an additional 1% in total government gross debt as a percentage of GDP leads to a reduction in the real GDP growth rate of 0.026%. These results change significantly when Nicaragua is included in the analysis, by virtue of the outliers presented in the debt / GDP ratio by the country for the years 1989 and 1990.
Keywords: Public Duet, Growth, Model DOLS